2018
DOI: 10.1111/acel.12830
|View full text |Cite|
|
Sign up to set email alerts
|

A salicylic acid derivative extends the lifespan of Caenorhabditis elegans by activating autophagy and the mitochondrial unfolded protein response

Abstract: Plant extracts containing salicylates are probably the most ancient remedies to reduce fever and ease aches of all kind. Recently, it has been shown that salicylates activate adenosine monophosphate‐activated kinase (AMPK), which is now considered as a promising target to slow down aging and prevent age‐related diseases in humans. Beneficial effects of AMPK activation on lifespan have been discovered in the model organism Caenorhabditis elegans (C. elegans). Indeed, salicylic acid and acetylsalicylic acid exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The ability of SA and its derivatives to induce autophagy is well explored in several other organisms ( Pietrocola et al, 2018 ; Shamalnasab et al, 2018 ). However, the role of SA in Plasmodium remains elusive.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of SA and its derivatives to induce autophagy is well explored in several other organisms ( Pietrocola et al, 2018 ; Shamalnasab et al, 2018 ). However, the role of SA in Plasmodium remains elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Statins, cholesterol-lowering drugs targeting the mevalonate pathway, have been shown to trigger the UPR mt [ 15 ]. Furthermore, a salicylic acid derivative, C8-SA, activates the UPR mt , and this response is associated with increased lifespan in C. elegans (Table 1 ) [ 16 ]. Through a screen of the C. elegans genome, a previous study showed that knockout of many mitochondrial process-related genes induced UPR mt , which explained the role of these genes in the maintenance of mitochondrial homeostasis (Table 2 ) [ 17 ].…”
Section: Inducers Of the Upr Mtmentioning
confidence: 99%
“…In fact, autophagy activation is a common hallmark among nutritional anti-aging interventions ( Madeo et al, 2015 ), although the causal involvement of this activation in the context of CR and fasting remains surprisingly poorly investigated and has mainly been investigated in C. elegans mutants that only exhibit CR-like responses ( Hansen et al, 2008 ). Nevertheless, autophagy is essential for the lifespan extending effects of AMP-activated kinase (AMPK) stimulation by salicylic acid derivatives ( Shamalnasab et al, 2018 ). Other AMPK agonists, like metformin have been shown to counteract aging-related inflammation (“inflammaging”) processes through autophagy activation ( Bharath et al, 2020 ).…”
Section: Targeting Autophagy To Delay Agingmentioning
confidence: 99%